La literatura femenina en los años sesenta: Incomodidades, temores y raras lecturas en "El escarabajo de oro" - Diz, Tania (2018)
This article analyses the ideas that emerge from the term "women´s writing" that circulates in cultural magazines in the sixties in Argentina. More specifically, it analyses Liliana Heker´s texts published in El escarabajo de oro. It then asks what ideas about sexual difference can be read and what aesthetic and ideological disputes are at play in questioning this notion. The analysis is based on the hypothesis that conservative ideas predominate with respect to sexual difference, although some fissures are glimpsed. The article also focuses on the discomfort that this question generates, the foundations that are used, how Virginia Woolf and Simone de Beauvoir are read, the prejudices against feminism and, finally, it proposes the figure of Silvina Bullrich as the counterexample of the woman writer of the time.